Weight Changes in Mandibular Fracture Patients After Maxillomandibular Fixation: Mandibular Fracture Patients After Maxillomandibular Fixation - Ashraf, Rutaba; Pervaiz, Benish; Uddin, Haseeb; Baluch, Raheela Aziz; Farooq, Muhammad Umar; Shar, Mor Khan (Pakistan Journal of Health Sciences, 2025)
Maxillofacial injuries, frequently caused by accidents or violence, often result in mandibular fractures. Treatment options include open and closed reduction, the latter utilising maxillomandibular fixation. Although maxillomandibular fixation is a cost-effective method, it may restrict normal dietary intake, leading to weight loss and potential malnutrition that can negatively impact recovery. Objective: To assess weight changes in mandibular fracture patients following maxillomandibular fixation. Methods: A comparative cross-sectional study was conducted at the Pakistan Institute of Medical Sciences from November 2023 to April 2024, enrolling 75 adult patients (ages 18-50) undergoing maxillomandibular fixation for mandibular fractures. Weight measurements were recorded preoperatively and at one and four weeks postoperatively. Statistical analysis was performed using SPSS Version 27.0. Results: The mean age of participants was 26.4 years, with 92% being male. The average preoperative weight was 63.08 kg, decreasing significantly to 58.57 kg after one week and 57.57 kg after four weeks (p<0.001). This weight loss was attributed to dietary restrictions and discomfort from jaw immobilisation. Conclusions: It was concluded that this study reveals significant weight loss post-maxillomandibular fixation, indicating a need for targeted nutritional support during recovery. These findings emphasize the importance of developing effective intraoperative and postoperative care protocols to meet nutritional needs, potentially enhancing recovery outcomes and quality of life for patients. Future research should explore the long-term effects of weight changes and interventions to mitigate weight loss during recovery.